In vitro drug interaction of ionophores with artemisinin and chloroquine against Plasmodium falciparum 3D7 blood-stage infection - Rajendran, Vinoth; Gurukkalot, Keerthana (Frontiers in Drug Discovery, 2023)
The prevalence of clinical resistance of P. falciparum towards artemisinin and its partner drugs has significantly hampered malarial chemotherapy. To circumvent this situation, identifying a new class of partner drugs with significant anti-malarial efficacy and multi-stage activity can slow the development of resistance. This study demonstrates the potential interactions of carboxylic ionophores such as monensin (MON), maduramicin (MAD) or salinomycin (SAL) with standard antimalarial drugs artemisinin (ART) or chloroquine (CQ). The in vitro drug interactions were studied in P. falciparum 3D7 strain by a growth inhibition SYBR green 1 assay. The asynchronized parasites were exposed for 48 h in the presence of varying proportions of two drug concentrations using the modified fixed-ratio isobologram method. We determined the growth inhibition response and the sums of the fractional inhibitory concentrations (ΣFICs) of the following drug combinations (4:1, 3:2, 2:3, 1:4) and (1:1, 1:3, 3:1) were calculated for 50% inhibitory concentrations (IC50s). Combining artemisinin with monensin, maduramicin, or salinomycin showed significant additive interaction. A combination of chloroquine with monensin, maduramicin, or salinomycin showed slight synergism to additive interaction. None of the drug combinations displayed an antagonistic effect indicating ionophores usage in combination therapy to treat drug-resistant malarial infections.